Potential Therapeutic Implications of Caffeic Acid in Cancer Signaling: Past, Present, and Future - Manzar Alam; Ghulam Md Ashraf; Kayenat Sheikh; Anish Khan; Sabeeha Ali; Md. Meraj Ansari; Mohd Adnan; Pasupuleti Visweswara Rao; Md. Imtaiyaz Hassan (Frontiers Media S.A., 2022)
Caffeic acid (CA) has been present in many herbs, vegetables, and fruits. CA is a bioactive compound and exhibits various health advantages that are linked with its anti-oxidant functions and implicated in the therapy and prevention of disease progression of inflammatory diseases and cancer. The anti-tumor action of CA is attributed to its prooxidant and anti-oxidant properties. CA’s mechanism of action involves preventing reactive oxygen species formation, diminishing the angiogenesis of cancer cells, enhancing the tumor cells’ DNA oxidation, and repressing MMP-2 and MMP-9. CA and its derivatives have been reported to exhibit anti-carcinogenic properties against many cancer types. CA has indicated low intestinal absorption, low oral bioavailability in rats, and pitiable permeability across Caco-2 cells. In the present review, we have illustrated CA’s therapeutic potential, pharmacokinetics, and characteristics. The pharmacological effects of CA, the emphasis on in vitro and in vivo studies, and the existing challenges and prospects of CA for cancer treatment and prevention are discussed in this review.